Interpretasi Makna Waka Berunsur Kata Naniwa dalam Hyakunin Isshu: Kajian Semiotik - Sulthon Hernanda, Muhammad; Novitasari, Raden (IZUMI, 2026)
This article took the field of semiotic research and focuses on interpretation of meanings of three Japanese poems/waka (和歌), that include the word ‘Naniwa’ (難波) from the famous Japanese poetry compilation, named Hyakunin Isshu (百人一首). The research conformed Michael Riffaterre's theory of semiotic readings, with procedure of: (1) heuristic reading, (2) hermeneutic reading, (3) matrix, model, variant, and (4) hypogram. This research used qualitative descriptive method, a research method that describes and illustrates linguistic phenomena. Heuristic reading produced referential meanings, while hermeneutic reading produced persuative meanings and indirect expressions due to the use of kakekotoba (掛詞), a pivotal vocabulary that is usually written only using hiragana letters, however its meaning refers to more than one vocabulary. The matrix on the 19th waka is "anxiety", then the matrix on the 20th waka is "sacrifice", and the matrix on the 88th waka is "love". Thus, the three matrices are realized into models, which took form of words or phrases written in the waka. Lastly, the models are shaped into variants that refers directly to the lines in the waka. The hypogram (intertextual relation) of the three waka referred to the word Naniwa which is clearly written using the same kanji: 難 (nan) and 波 (wa). Ultimately, kakekotoba had a significant role on increasing the persuasive element of those three waka, as well as influencing the interpretation of their meanings. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor